Chemical Biology & Biochemistry Laboratory Using Genetic Code Expansion Manual - Mehl, Ryan; van Zee, Kari; Kean, Kelsey (Open textbook library., 2019)
Chemical Biology & Biochemistry Laboratory Using Genetic Code Expansion Manual